Frequency and characteristics of myocardial ischemia recorded during stress echocardiography in patients with high coronary risk - Ilić Stevan; Deljanin-Ilić Marina; Stoičkov Viktor (Vojnosanitetski Pregled, 2011)
Background/Aim. Ischemic heart disease is the major cause of morbidity and mortality in the world as well as in our country. Ischemic heart disease has the multifactorial origin and the presence of several risk factors increases the risk of myocardial ischemia. The aim of the study was to evaluate the frequency and characteristics of myocardial ischemia in asymptomatic subjects with two or more risk factors for coronary artery disease during stress echocardiography. Methods. In 240 high risk asymptomatic subjects (an absolute risk of fatal cardiovascular disease of more than 5%, according to the Systemic Coronary Risk Evaluation Chart), the exercise stress echocardiography test was performed. The criterion for myocardial ischemia was the appearance of transient segmental wall motion abnormality (WMA). The wall motion score index was calculated before and after the exercise stress echocardiography. Results. During exercise stress echocardiography, in 36 (15%) subjects WMA occurred. Out of 36 subjects with myocardial ischemia, in 10 (27.8%) subjects WMA and ST segment depression were accompanied with the first occurrence of chest pain (the subgroup with symptomatic myocardial ischemia), in 20 (55.6%) subjects WMA and ST segment depression were detected and in 6 (16.6%) subjects only WMA occurred (the subgroup with silent myocardial ischemia). There were no significant differences between the subgroups with symptomatic and silent myocardial ischemia with regard to exercise tolerance, heart rate at the onset of WMA, and time to the onset of WMA, but the wall motion score index was significantly higher in the subjects with symptomatic myocardial ischemia (p < 0.01). In all the individuals with symptomatic myocardial ischemia, significant stenosis of the coronary arteries was found by coronary angiography. Out of 26 subjects with asymptomatic myocardial ischemia, coronary angiography was performed in 18 and significant stenosis of the coronary arteries was diagnosed in all of them. The number and grade of coronary stenosis in subjects with symptomatic and silent myocardial ischemia were similar. Conclusion. The obtained results presented the incidence of myocardial ischemia in 15% of asymptomatic subjects with high coronary risk during stress echocardiography. Silent myocardial ischemia was markedly more frequent than symptomatic one, but in the subjects with symptomatic ischemia, the wall motion score index was significantly higher.